2017
DOI: 10.1186/s13008-017-0033-x
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles of CDK12 in tumorigenesis

Abstract: Cyclin-dependent kinases (CDKs) are key regulators of both cell cycle progression and transcription. Since dysregulation of CDKs is a frequently occurring event driving tumorigenesis, CDKs have been tested extensively as targets for cancer therapy. Cyclin-dependent kinase 12 (CDK12) is a transcription-associated kinase which participates in various cellular processes, including DNA damage response, development and cellular differentiation, as well as splicing and pre-mRNA processing. CDK12 mutations and amplif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 69 publications
(142 reference statements)
3
59
0
Order By: Relevance
“…The set of 20 consensus genes encompassed many well-known genes with the potential to distinguish subtypes. In addition to three pam50 genes; ERBB2, ESR1 and FOXA1 (Parker, et al, 2009), the consensus set included; C1orf64 (ER-related factor, ERRF) which was down-regulated in TNBC, in accordance with literature (Naderi, 2017;Su, et al, 2012), CDK12, which was up-regulated in Her2 samples, supported by literature indicating that a total of 71% of Her2-enriched tumours over-express this gene (Paculova and Kohoutek, 2017). Other genes of interest were CYP2B6 (Lo, et al, 2010), MYLK3 (D'Amato, et al, 2015 and SLURP1 (Gao, et al, 2014).…”
Section: Case Study 1: Analysis Of Single-channel Microarray Data -Vasupporting
confidence: 72%
“…The set of 20 consensus genes encompassed many well-known genes with the potential to distinguish subtypes. In addition to three pam50 genes; ERBB2, ESR1 and FOXA1 (Parker, et al, 2009), the consensus set included; C1orf64 (ER-related factor, ERRF) which was down-regulated in TNBC, in accordance with literature (Naderi, 2017;Su, et al, 2012), CDK12, which was up-regulated in Her2 samples, supported by literature indicating that a total of 71% of Her2-enriched tumours over-express this gene (Paculova and Kohoutek, 2017). Other genes of interest were CYP2B6 (Lo, et al, 2010), MYLK3 (D'Amato, et al, 2015 and SLURP1 (Gao, et al, 2014).…”
Section: Case Study 1: Analysis Of Single-channel Microarray Data -Vasupporting
confidence: 72%
“…We see mutations in oncogenes and tumor-suppressor genes in HepG2, such as NRAS (Pylayeva-Gupta et al 2011), STK11/LKB1 (Zhou et al 2014), and PREX2 (Berger et al 2012;Yang et al 2016), as well as in the Wnt-pathway gene CTNNB1 due to the presence of either HepG2-specific protein-altering changes or small-scale structural changes (Table S5, Table S6, Dataset 1, Dataset 4, Supplemental Data). Moreover, we also identified mutations in genes recently found to play critical roles in driving cancer such as CDK12 (Paculová and Kohoutek 2017) and IKBKB (Xia et al 2012;Kai et al 2014). These mutations also implicate the dis-regulation of their associated molecular pathways in HepG2.…”
Section: Discussionmentioning
confidence: 99%
“…The gene overlap between HepG2 PPA and the Sanger Cancer Gene Census is 19 (Table S6). HepG2 PPA variants include oncogenes and tumor suppressors such as NRAS (Pylayeva-Gupta et al 2011), STK11/LKB1 (Zhou et al 2014), and PREX2 (Berger et al 2012;Yang et al 2016) as well as other genes recently found to play critical roles in driving cancer such as CDK12 (Paculová and Kohoutek 2017) and IKBKB (Xia et al 2012;Kai et al 2014). RP1L1, which was recently found to be significantly mutated in hepatocellular carcinoma (Cancer Genome Atlas Research Network 2017) is also present among the PPA variants.…”
Section: Snvs and Indelsmentioning
confidence: 99%
“…CDK12 has roles in the DNA damage response as well as in cellular and developmental differentiation; however, the exact mechanism by which CDK12 acts in the transcriptional regulation of these genes is not yet fully understood. Overexpression of CDK12 has been demonstrated in breast and ovarian carcinogenesis, but has not yet been investigated in OSCC …”
Section: Cdks and Oral Carcinogenesismentioning
confidence: 99%
“…Overexpression of CDK12 has been demonstrated in breast and ovarian carcinogenesis, but has not yet been investigated in OSCC. 39 Overexpression of CDKs, in particular CDK4 and CDK6, has been shown to contribute to cell cycle dysfunction in a range of cancer types. Currently, there is minimal evidence regarding the role of CDKs in the development and progression of OSCC; however, we suggest that it is a promising area of investigation.…”
Section: Cdk S and Or Al C Arcinog Ene S Ismentioning
confidence: 99%